2D-arrrays of Cu Nanodisks on Anodic Aluminum Oxide (AAO) Template for SERS Applications - Thi Yen Mai, Nguyen (VNU Journal of Science: Mathematics - Physics; Vol 34 No 4DO - 10.25073/2588-1124/vnumap.4309, 2019)
Abstract. Copper nanodisks (Cu NDs) of 50 nm in size were prepared on square-inch anodic aluminum oxide substrates by RF-sputtering method. The samples were annealed at 450 o C, then the walls of anodic aluminum oxide (AAO) substrates were lift off in a solution of acid phosphoric. The 2D arrays of Cu NDs were fabricated in high quality. Morphology of the substrates was observed by scanning electron microscopy. Surface plasmon resonance absorption was observed with different peaks in the range of 400-1400nm wavelengths that means the substrate is promising for SERS application.  The Raman spectrum of Rhodamine 6G loaded on AAO substrates was much enhanced.   Keyword: Anodic aluminum oxide (AAO) tempelate, Cu nanodisk, SERS References [1] Schieberle P and Molyneux RJ 2012 J. Agric. Food. Chem. 2404-8 [2] Das RS and Agrawal YK 2011 Vib. Spectrosc. 163-76 [3] Yang D and Ying Y 2011 Appl. Spectrosc. Rev. 539-60 [4] Fleischmann M, Hendra PJ and Mc Quillan AJ 1974 Chem. Phys. Lett. 163-6 [5] Gersten J and Nitzan A 1980 J. Chem. Phys. 3023-37 [6] Moskovits M 1985 Rev. Mod. Phys. 783-826 [7] Masuda H and Fukuda K 1995 Science 268 1466 [8] Thi Thuy Nguyen et al 2016 Adv. Nat. Sci: Nanosci. Nanotechnol. 7 045017